2009
DOI: 10.1002/cbf.1539
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of human paraoxonase and PON 1 L/M55–PON 1 Q/R 192 polymorphisms in Turkish patients with coronary artery disease

Abstract: Paraoxonase 1 (PON 1) is a high-density lipoprotein (HDL)-associated enzyme with antioxidant function protecting low-density lipoprotein (LDL) from oxidation. PON 1 has two amino acid polymorphisms in coding region; L/M 55 and Q/R 192. These polymorphisms modulate paraoxonase activity of the enzyme. PON 1 activity decreases in coronary artery disease (CAD). In the present study, distribution of PON 1 L/M 55 and Q/R 192 polymorphisms and the effect of these polymorphisms on the activities of PON 1, and on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 25 publications
3
11
4
Order By: Relevance
“…Kaman et al also studied the PON55 polymorphism in an angiographically-defined Turkish population and did not find an association between the severity of CAD and PON55 polymorphism. 25 In contrast to the results of the present study, they reported that the frequency of M allele was significantly higher among control subjects than among CAD patients. The difference in the frequency of polymorphic M allele between these two studies including Turkish populations may arise from the different sample sizes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Kaman et al also studied the PON55 polymorphism in an angiographically-defined Turkish population and did not find an association between the severity of CAD and PON55 polymorphism. 25 In contrast to the results of the present study, they reported that the frequency of M allele was significantly higher among control subjects than among CAD patients. The difference in the frequency of polymorphic M allele between these two studies including Turkish populations may arise from the different sample sizes.…”
Section: Discussioncontrasting
confidence: 99%
“…The difference in the frequency of polymorphic M allele between these two studies including Turkish populations may arise from the different sample sizes. Although the study population of the report by Kaman et al was larger than the population in the present study, the CAD patients with diabetes were excluded in the present study but not in the study by Kaman et al 25 The studies investigating the relation between the PON192 polymorphism and CAD have also shown conflicting results even among the studied populations within the same country. 6,17,18,22,[26][27][28] In the present study, the evaluation of PON192 genotype distribution between healthy controls and CAD patients did not show any significant difference PON192 polymorphism in Turkish populations also showed no significant difference in the distribution of PON192 genotypes or alleles between CAD patients and controls.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The PON1 55 LL genotype was reported to be associated with a 1.78-fold increase in the risk of ischemic stroke in a Turkish population (Demirdogen et al 2009;Kaman et al 2009), with the highest PON activities detected in the LL and RR genotypes (Kaman et al 2009). The frequency of the QQ genotype of PON1 192 and the MM genotype of PON1 55 was reported to be lower in patients compared with healthy control subjects.…”
Section: Discussionmentioning
confidence: 96%
“…Ethnic differences may also play a role, as it has been reported that in a Turkish patient population PON-1 L55M was associated with CHD but not PON-1 Q192R (38). The PON-1 Gln192Arg SNP has been associated with a significantly increased risk of stroke (39).…”
Section: Pon Polymorphisms and Atherosclerosismentioning
confidence: 95%